2004
DOI: 10.1177/0886109903262772
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Constellations and Dynamics of Low-Income Rural Mothers

Abstract: To address the policy debate surrounding the use of funds from Temporary Assistance to Needy Families for marriage-promotion activities, this article profiles the nature of low-income rural mothers' relationships with their partners and the nonresidential fathers of their children. It presents the results of interviews with 35 lowincome mothers from two rural Maryland counties. Although the analyses revealed that the presence of a male partner was not related to a mother's economic or emotional well-being, oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…It has been suggested rural families may play a greater role in children's development than urban families because of the greater isolation of families in rural areas [42] and also because social networks in rural areas are more likely to be kin-based than those in urban areas [43]. In turn, rural children may have less access to inluences outside the family.…”
Section: Home Level Diferencesmentioning
confidence: 99%
“…It has been suggested rural families may play a greater role in children's development than urban families because of the greater isolation of families in rural areas [42] and also because social networks in rural areas are more likely to be kin-based than those in urban areas [43]. In turn, rural children may have less access to inluences outside the family.…”
Section: Home Level Diferencesmentioning
confidence: 99%
“…Because of this isolation, it has been suggested that the qualities of rural families may play a greater role in children's development than do the qualities of urban families (Marotz-Baden, Hennon, & Brubaker, 1988;Vernon-Feagans & Cox, 2013). Another consequence is that social networks in rural areas are more likely to be kin-based (Kohler, Anderson, Oravecz, & Braun, 2004). Rural children may thus have less access to influences outside the family, resulting in a greater influence from their own families.…”
Section: Rural Socio-economic and Cultural Determinants Of Language Amentioning
confidence: 99%
“…Comparisons should be made with similar samples of urban residents because these results may provide additional support for considering rurality as a unique context of human development (Simmons et al, 2007b). Kohler et al (2004) suggest that social workers be schooled in integrating informal family support into service delivery plans. Social workers and family service professionals can play key roles in addressing policy implications of this research.…”
Section: Summary and Public Policy Recommendationsmentioning
confidence: 99%
“…Many mothers shared information on how family, friends, and churches supported them in times of need. Such support included giving objective opinions, being there when needed, and sending help when asked (Kohler, Anderson, Oravecz, & Braun, 2004). Simmons, Braun, Wright, and Miller (2007) reported that a model of economic well-being that included both social support and human capital provided a better fit for the data, as social support was a key contributor to long-term success of rural families.…”
mentioning
confidence: 99%
See 1 more Smart Citation